Picturing Royal Charisma Kings and Rulers in the Near East from 3000 BCE to 1700 CE - David, Arlette; Milstein, Rachel; Ornan, Tallay (2023)
Picturing Royal Charisma assesses how Middle Eastern leaders manipulated visuals to advance their rule from around 4500 BC to the 19th century AD. In nine fascinating narratives, it showcases the dynamics of long-lasting Middle Eastern traditions, dealing with the visualization of those who stood at the head of the social order. The contributions discuss: Mesopotamian kings who cast themselves as divine representatives in art; the relationships between the 'king of men' and 'king of beasts' - the lion; Akhenaten's visual conception of a divine king without hybrid attributes; the royal image as guiding movements of visitors in the palace of Nimrud; continuities in the functions and representation of Neo-Assyrian eunuchs that survived in the Achaemenid, Sasanian, Byzantine and Islamic courts; the triumphal arch of the emperor Titus and its reflections in Christian Constantinople; patterns of authority and royal legitimacy in 3rd century AD Palmyra and Rome; the use of the Biblical past in the construction of kingship in 12th century Crusader Jerusalem; and the use of 'the power of images' by Islamic rulers, adopting visuals of thrones and throne-rooms despite Islamic opposition to the figurative portrayal of kings.